Descriptive cohort trial of terminal patients in medical home care in Bogotá – 2008–2012 - Támara, Liliana M. (Colombian Journal of Anesthesiology, 2014)
Introduction: Palliative care for end-of-life patients in Bogotá is still in the process of consolidation. This type of care demands high technical and scientific standards, in addition to supporting the patient and family in making end-of-life ethical decisions, particularly with respect to sedation, hydration and feeding. Methodology: Statistical descriptive analysis of a cohort comprised of 164 terminally ill patients treated in private practice in Bogotá between 2008 and 2012. Results: Out of the 90 patients who received care until their demise, the average age was 77 years old, including 63% women, 30%, university students, 41% widowers, and 84% Catholics. 8 patients had no medical insurance. 52% of the patients were cancer patients, 91% received home care, the average number of care days was 45 and the usual route of administration of medicines was subcutaneous. The most commonly used drugs were tramadol, ranitidine and midazolam. 73% of the patients required superficial sedation. In some cases, feeding and hydration were administered through alternate routes and in others were discontinued. Analysis: there is a need to study the conditioning factors for private medical home care and for maintaining this type of care until the end of life. Characterizing this population enables the identification of some useful information for the administration of end-of-life care in the country.